YAP orchestrates heterotypic endothelial cell communication via HGF/c-MET signaling in liver tumorigenesis - Thomann, Stefan; Weiler, Sofia Maria Elisabeth; Marquard, Simone; Rose, Fabian; Ball, Claudia R.; Tóth, Marcell; Wei, Teng; Sticht, Carsten; Fritzsche, Sarah; Rössler, Stephanie; Torre, Carolina de la; Ryschich, Eduard; et al. (Cancer research, 2020)
The oncogene yes-associated protein (YAP) controls liver tumor initiation and progression via cell extrinsic functions by creating a tumor-supporting environment in conjunction with cell autonomous mechanisms. However, how YAP controls organization of the microenvironment and in particular the vascular niche, which contributes to liver disease and hepatocarcinogenesis, is poorly understood. To investigate heterotypic cell communication, we dissected murine and human liver endothelial cell (EC) populations into liver sinusoidal endothelial cells (LSEC) and continuous endothelial cells (CEC) through histomorphological and molecular characterization. In YAPS127A-induced tumorigenesis, a gradual replacement of LSECs by CECs was associated with dynamic changes in the expression of genes involved in paracrine communication. The formation of new communication hubs connecting CECs and LSECs included the hepatocyte growth factor (Hgf)/c-Met signaling pathway. In hepatocytes and tumor cells, YAP/TEA domain transcription factor 4 (TEAD4)-dependent transcriptional induction of osteopontin (Opn) stimulated c-Met expression in EC with CEC phenotype, which sensitized these cells to the promigratory effects of LSEC-derived Hgf. In human hepatocellular carcinoma, the presence of a migration-associated tip-cell signature correlated with poor clinical outcome and the loss of LSEC marker gene expression. The occurrence of c-MET-expressing CECs in human liver cancer samples was confirmed at the single-cell level. In summary, YAP-dependent changes of the liver vascular niche comprise the formation of heterologous communication hubs in which tumor cell-derived factors modify the cross-talk between LSECs and CECs via the HGF/c-MET axis.YAP-dependent changes of the liver vascular niche comprise the formation of heterologous communication hubs in which tumor cell-derived factors modify the cross-talk between EC subpopulations.